Regulators in Conflict: When Urgent Matters Conceal Efficiency (Observatorio Económico, 2007)
Confusing or multiple mandates in economic policy can generate serious conflicts of interest among regulators and lead to the abandonment of tasks that are essential to society's welfare, not through ill-intentioned neglect, but through excessive zeal in a few duties. This occurs, for example, when political tasks and technical tasks are carried out by the same ministry and price regulation is used as a means of accomplishing the political tasks. Continue reading...
Keywords: Conflicts of interest; Economic policy